Answer:
The answer is ∅ ⇒ no solution
Step-by-step explanation:
* Lets revise how to solve the system of equation by using
substitution method
- At first find a variable in terms of the other one from the
first equation
- Then substitute this value in the second equation
- So you can solve the equation because it has one variable
- After that put the value of the variable in the substitution
equation to find the second variable
* Now lets solve our problem
∵ x - y = 0 ⇒ (1)
∵ x - y - 2 = 0 ⇒ (2)
- Find x in terms of y from 1st equation
∴ x = y
- Substitute this value in the second equation
∴ y - y - 2 = 0
∴ 0 - 2 = 0 ⇒ -2 = 0
* But -2 ≠ 0, that means L.H.S ≠ R.H.S
∴ There is no solution for this system of equations
∴ The answer is ∅